(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The spread of COVID-19 in Mali represents a new challenge after years of instability, security threats and endemic corruption. The fragility of the health system and the limited measures taken to contain the disease might lead to severe consequences, while fearing further economic distress. At the same time, social and political tensions are rising and the legitimacy of President Keïta is put into question by a group of political opponents, the Mouvement du 5 Juin, led by a prominent religious leader.